Mechanics of cell sheets: plectin as an integrator of cytoskeletal networks - Zuzana Outla; Magdalena Prechova; Katerina Korelova; Jakub Gemperle; Martin Gregor (Open Biology)
Epithelia are multicellular sheets that form barriers defining the internal and external environments. The constant stresses acting at this interface require that epithelial sheets are mechanically robust and provide a selective barrier to the hostile exterior. These properties are mediated by cellular junctions which are physically linked with heavily crosslinked cytoskeletal networks. Such hardwiring is facilitated by plakins, a family of giant modular proteins which serve as ‘molecular bridges’ between different cytoskeletal filaments and multiprotein adhesion complexes. Dysfunction of cytoskeletal crosslinking compromises epithelial biomechanics and structural integrity. Subsequent loss of barrier function leads to disturbed tissue homeostasis and pathological consequences such as skin blistering or intestinal inflammation. In this article, we highlight the importance of the cytolinker protein plectin for the functional organization of epithelial cytoskeletal networks. In particular, we focus on the ability of plectin to act as an integrator of the epithelial cytoarchitecture that defines the biomechanics of the whole tissue. Finally, we also discuss the role of cytoskeletal crosslinking in emerging aspects of epithelial mechanobiology that are critical for the maintenance of epithelial homeostasis.